The Importance of Learning an English Language: The Importance of Learning an English Language - Qobilova, Kamola (Журнал иностранных языков и лингвистики, 2022)
Learning a second language is a requirement as we all enter the globalized era. In the age of globalization, everyone must wrestle if they want to develop and not stagnate. The advantages of learning a foreign language are not far off the mark; yet, as an advantage, this is construed more narrowly. By mastering other languages, one may communicate more effectively, allowing for more open perspectives in information technology, and they will undoubtedly have greater capital to move into a world where technical advancement is always moving forward. You will learn various causes and benefits if you can master a foreign language.